2014
DOI: 10.1016/j.gca.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacity, configurational heat capacity and fragility of hydrous magmas

Abstract: International audienceThe glassy and liquid heat capacities of four series of dry and hydrous natural glasses and magma as a function of temperature and water content (up to 19.9 mol%) were investigated using differential scanning calorimetry (DSC). The analyzed compositions are basalt, latite, trachyte and pantellerite. The results of this study indicate that the measured heat capacity of glasses (Cpg) is a linear function of composition and is well reproduced by the empirical model of Richet (1987). For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 96 publications
(196 reference statements)
2
25
0
Order By: Relevance
“…At the temperatures of interest here, the functional form of equation is an approximation of the transition from a thermal diffusivity by phonon interactions at intermediate temperatures to a diffusivity controlled by photon conduction at high temperatures [ Berman , ; Lee and Kingery , ]. Diffusivity and conductivity are approximately proportional when the temperature dependence of the conductivity is much greater than that of the density or specific heat capacity, which has been shown to be true in natural glasses [ Lange and Carmichael , ; Bagdassarov and Dingwell , ; Di Genova et al ., ]. We acknowledge that the high‐temperature limits to D ( T ) are potentially unreliable and suggest that they warrant further investigation for silicate materials relevant to geoscience problems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the temperatures of interest here, the functional form of equation is an approximation of the transition from a thermal diffusivity by phonon interactions at intermediate temperatures to a diffusivity controlled by photon conduction at high temperatures [ Berman , ; Lee and Kingery , ]. Diffusivity and conductivity are approximately proportional when the temperature dependence of the conductivity is much greater than that of the density or specific heat capacity, which has been shown to be true in natural glasses [ Lange and Carmichael , ; Bagdassarov and Dingwell , ; Di Genova et al ., ]. We acknowledge that the high‐temperature limits to D ( T ) are potentially unreliable and suggest that they warrant further investigation for silicate materials relevant to geoscience problems.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout, we take ρ , C p , and h to be negligibly dependent on temperature and use constant values of ρ = 2000 kg m −3 [ Lange and Carmichael , ], C p = 1000 J kg −1 K −1 [ Di Genova et al ., ], and h = 100 W m −2 K −1 [ Stroberg et al ., ]; these values are typical of anhydrous silicate liquids. Of these parameters, h is the least well constrained in our work because its value depends on whether the convection at the particle rim is forced or natural, which in turn depends on wind conditions or particle velocities relative to the plume gas [ Stroberg et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…Our dataset, including data sources, is described in Table 1 (e.g., Bouhifd et al, 2006Bouhifd et al, , 2013Giordano et al, 2015;Di Genova et al, 2014;Robert et al, 2014) and the full oxide chemical compositions are reported in Table A1 (Supplementary Materials). Fig.…”
Section: The Datamentioning
confidence: 99%
“…Measured values of viscosity are from 10 −1 to 10 14 Pa s. These experiments commonly use an anhydrous melt as a base composition to which volatiles have been added. In general, the hydrous melts were synthesized at elevated pressure and temperature below their solubility limits and quenched isobarically to produce homogeneous unvesiculated hydrous glasses (e.g., Richet and Bottinga, 1995;Richet and Toplis, 2001;Di Genova et al, 2014). The viscosity measurements for hydrous silicate melts are restricted to a narrower range of temperatures immediately above their respective glass transition temperatures to avoid syn-experiment vesiculation or crystallization.…”
Section: The Datamentioning
confidence: 99%
“…The physico-chemical properties of silicate melts that govern magmatic and volcanic processes (melt generation, transport, and emplacement on the terrestrial planets) now have a long history of investigation (e.g., Richet 1984;Lange andCarmichael 1987, 1990;Persikov et al 1990;Dingwell et al 1996;Hess and Dingwell 1996;Papale 1999;Romano et al 2001;Whittington et al 2001;Dingwell 2006;Neuville 2006;Behrens and Zhang 2009;Di Genova et al 2014a;Robert et al 2014;Sehlke et al 2014).…”
Section: Introductionmentioning
confidence: 99%